2004
DOI: 10.1016/s0002-9440(10)63764-9
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast Differentiation Is Induced in Keratinocyte-Fibroblast Co-Cultures and Is Antagonistically Regulated by Endogenous Transforming Growth Factor-β and Interleukin-1

Abstract: In wound healing epidermal-dermal interactions are known to regulate keratinocyte proliferation and differentiation. To find out how fibroblasts respond to epithelial stimuli, we characterized fibroblasts in monolayer co-culture with keratinocytes. On co-culture numerous extracellular matrix- and smooth muscle cell-associated gene transcripts were up-regulated in fibroblasts, suggesting a differentiation into myofibroblasts. Increased alpha-smooth muscle actin (alpha-SMA) protein expression in co-cultured fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 50 publications
8
122
0
9
Order By: Relevance
“…In contrast, in a study utilizing a coculture model of keratinocytes and dermal fibroblasts, myofibroblast differentiation was TGF-β dependent but was antagonized by IL-1β (52). The discrepancy between these 2 studies likely represents inherent cell type-specific differences between airway and dermal fibroblasts.…”
Section: Figurementioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, in a study utilizing a coculture model of keratinocytes and dermal fibroblasts, myofibroblast differentiation was TGF-β dependent but was antagonized by IL-1β (52). The discrepancy between these 2 studies likely represents inherent cell type-specific differences between airway and dermal fibroblasts.…”
Section: Figurementioning
confidence: 90%
“…*P < 0.05; **P < 0.001. link innate immune responses to subsequent adaptive immune responses, ultimately promoting wound repair (50). Thus, the induction of IL-1β that occurs during SM of the airway epithelium may act as both an autocrine factor to influence gene expression to facilitate cell migration and wound closure and as a paracrine factor to recruit inflammatory cells and to induce matrix production and contractility of adjacent fibroblasts (51,52). The basal, suprabasal, and superficial cells of SM in COPD all express increased IL-1β, suggesting that both increased luminal and basal secretion of IL-1β are provided by the squamous metaplastic epithelium.…”
Section: Figurementioning
confidence: 99%
“…This is the first study showing the inhibition of CMF differentiation by IL-1α. Earlier studies using co-cultures of keratinocytes and dermal fibroblasts showed that TGFβ1-induced αSMA expression was suppressed by IL-1α (Shephard et al, 2004). Moreover, blocking the IL-1 receptor potentiated αSMA expression in the dermal fibroblasts, indicating an inhibitory effect of IL-1 on TGFβ1-induced myofibroblast differentiation (Shephard et al, 2004).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Earlier studies using co-cultures of keratinocytes and dermal fibroblasts showed that TGFβ1-induced αSMA expression was suppressed by IL-1α (Shephard et al, 2004). Moreover, blocking the IL-1 receptor potentiated αSMA expression in the dermal fibroblasts, indicating an inhibitory effect of IL-1 on TGFβ1-induced myofibroblast differentiation (Shephard et al, 2004). In human pulmonary fibroblasts, TGFβ1-induced αSMA expression was inhibited by TNFα, indicating that other pro-inflammatory cytokines show similar inhibitory effects on myofibroblast differentiation (Liu et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Cytoskeleton proteins, ECM molecules, Cytokines and Nucleus proteins which are elements of Epithelial Mesenchymal Transition (EMT), which are commonly associated with OSMF, lead to the possibility of EMT being a part of fibrosis of oral mucous, which is triggered by betel quid chewing habit in OSMF [6]. Extensive myofibroblast differentiation requires close contact between keratinocytes and fibroblasts, which suggests their role in cellular signaling in dermal wounds [7].…”
Section: Introductionmentioning
confidence: 99%